2023
DOI: 10.1177/20563051231177964
|View full text |Cite
|
Sign up to set email alerts
|

Transgressive Play and the Inherent Limits of Business Growth for China’s LGBTQ Platforms: The Case of a Social Game in Aloha

Abstract: Since 2016, China’s online LGBTQ platforms, such as Blued and Aloha, have been seeking to increase user acquisition and retention by introducing new functionalities to their interfaces. Although these attempts were promising at first, most of their endeavors proved unsustainable, largely due to the condition in which their businesses operate: a niche audience segment in a winner-take-all mobile market and a highly regulatory market in which LGBTQ content is often made a site for the execution of power. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Past studies showed information quality, personalization, engagement, and presence impact perceived social worth. With few game developers dominating, understanding social value remains pivotal to sustained competitiveness and market expansion (Wang, 2023). As defined in the perceived value framework, social factors greatly mold user perspectives, attitudes, and spending via elements like presence, status, and virtual item ownership.…”
Section: Price Valuementioning
confidence: 99%
“…Past studies showed information quality, personalization, engagement, and presence impact perceived social worth. With few game developers dominating, understanding social value remains pivotal to sustained competitiveness and market expansion (Wang, 2023). As defined in the perceived value framework, social factors greatly mold user perspectives, attitudes, and spending via elements like presence, status, and virtual item ownership.…”
Section: Price Valuementioning
confidence: 99%